2022
DOI: 10.1002/dc.25021
|View full text |Cite
|
Sign up to set email alerts
|

The necessity of continuing cervical cancer screening of elderly Korean women aged 65 years or older

Abstract: Background Although the incidence of cervical cancer has decreased since the 1980s in Korea, it remains high among the elderly women. This study evaluated the suitability of cervical cancer screening for elderly Korean women aged ≥65 years according to recommendations by the American Society of Cytopathology and American Society for Colposcopy and Cervical Pathology. Methods We retrospectively reviewed the records of patients who underwent cervical cancer screening, followed by liquid‐based Pap test, human pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The findings indicated that there is a serious burden of cervical cancer among elderly women in Lingang New Area. In fact, the burden of cervical cancer among elderly women is also significant in America ( Cooley et al, 2023 , Qin et al, 2023 ), Korea ( Cho et al, 2022 ), and other regions in China ( Liu et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that there is a serious burden of cervical cancer among elderly women in Lingang New Area. In fact, the burden of cervical cancer among elderly women is also significant in America ( Cooley et al, 2023 , Qin et al, 2023 ), Korea ( Cho et al, 2022 ), and other regions in China ( Liu et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%